An overview of oxidative and photooxidative decolorisation treatments of textile waste waters - (:unkn) unknown (Society of Dyers and Colourists, 1997)
Oxidative and photooxidative decolorisation of textile weste waters have been investigated and it has been determined that simultaneous application of ultraviolet irradiation with hydrogen peroxide or ozone increases oxidation rate and strength of oxidation. The waste water quickly loses its colour and the noxious chemicals rapidly degrade to a degree that the treated water may be reused. The treatment process is, however, quite costly and this technique is currently only advisable for noxious and recalcitrant compounds when the cost factor is of secondary concern.